2017
DOI: 10.1016/j.intman.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Chinese expatriate management in emerging markets: A competitive advantage perspective

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 63 publications
(82 reference statements)
1
48
0
Order By: Relevance
“…Furthermore, this study also found that human resource management practices had an indirect effect on competitive advantage. These findings are supported by research findings Rui et al (2017) and Ellitan (2004). Regarding the effect of safety culture, the findings are supported by Rechenthin (2004) and Fernández-Muñiz et al (2009).…”
Section: Managerial Implications and Conclusionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, this study also found that human resource management practices had an indirect effect on competitive advantage. These findings are supported by research findings Rui et al (2017) and Ellitan (2004). Regarding the effect of safety culture, the findings are supported by Rechenthin (2004) and Fernández-Muñiz et al (2009).…”
Section: Managerial Implications and Conclusionsupporting
confidence: 82%
“…Also, multidimensional human resource management practices are believed to influence the shape work safety culture in companies (Chuang, 2013). Work safety culture which is a perception of various aspects of safety in the work environment can only function if human resource management practices are carried out following company strategies that have a high commitment to work safety (Rui et al, 2017;Handoko et al, 2015). Furthermore, Ployhart et al (2011) theorize that human resource management practices such as training creating knowledge and skills improve the ability of the workforce which in turn will increase their productivity.…”
Section: Human Resource Management Practicesmentioning
confidence: 99%
“…To mitigate these challenges and bridge the local workforce's knowledge gap, MNCs expand their innovative talent pool by recruiting and assigning expatriates to foreign host countries to build capacity, transform the subsidiary's work methods and train employees on technology use (Rose et al, ). These responsibilities demand innovative solutions that make EIB an essential factor for expatriates' success (Caligiuri & Day, ; Rose et al, ; Rui et al, ). In support of this statement, Dabic et al () noted that expatriates play an essential role in MNCs' innovation endeavours by injecting new perspectives into existing problems.…”
Section: Discussionmentioning
confidence: 99%
“…Employees' innovative behaviour refers to their inclination to generate, promote and implement useful ideas concerning new or improved services, products and processes (Janssen, ). To mitigate the difficulties associated with acquiring employees with a higher innovative behaviour, who are generally scarce, from the local market, companies broaden their pool and hire expatriates from the international labour market (Dabic et al, ; Dickmann & Harris, ; Kratzer, Leenders, & Van Engelen, ; Rui, Zhang, & Shipman, ). Expatriates provide innovative ideas and perspectives that can bridge the skills gap of local employees (Caligiuri & Day, ; Rose et al, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous research suggests workers were expatriated to break the local norms regarding working conditions. While expatriated workers may embody a special work ethic of hard work and self‐sacrifice—which has been suggested as the competitive advantage of Chinese MNCs (Rui et al, )—we need to be cautious with such essentialist and culturalist explanations. Work ethics come out of intensive competition for work in China, coercive forms of labor control (Lee, ), and a probusiness legal framework (Gallagher & Dong, ).…”
Section: Resultsmentioning
confidence: 99%